The Effect of Integrated Learning Management Systems FLearn in Improving Learning Outcomes at Universities during Online Learning - Sanoto, Herry; Kusuma, Dani; Paseleng, Mila Chrismawati (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2023)
The problem in learning during the covid-19 pandemic is how the university implements effective online learning for students. In order to facilitate online learning to be more comprehensive and integrated, the development of an integrated learning system, namely the learning system in Flexibel Learning or Leaning management, is expected to increase the effectiveness of online learning. The research method in this study is a mixed-method research method with a sequential exploratory model. The research begins with a qualitative study to find the root of the problem and then continues with quantitative analysis to find the influence between variables. The study subjects were fourth-year students in the mathematics education study program. The study results show that the integration of the system facilitates the implementation of learning in the online learning process, but there are still obstacles, such as internet access and learning devices. In contrast, the regression test results show a significant influence between the integration of the learning system on student learning outcomes. The influence of learning system integration on learning achievement is 61.3%, and 38.7% is affected by other factors such as motivation, learning independence, student responsibility, and adequate internet access.